Phylogenetic differences in calcium permeability of the auditory hair cell cholinergic nicotinic receptor - Lipovsek, Maria Marcela (2012)
The a9 and a10 cholinergic nicotinic receptor subunits assemble to form the receptor that mediates efferent inhibition of hair cell function within the auditory sensory organ, a mechanism thought to modulate the dynamic range of hearing. In contrast to all nicotinic receptors, which serve excitatory neurotransmission, the activation of a9a10 produces hyperpolarization of hair cells. An evolutionary analysis has shown that the a10 subunit exhibits signatures of positive selection only along the mammalian lineage, strongly suggesting the acquisition of a unique function. To establish whether mammalian a9a10 receptors have acquired distinct functional properties as a consequence of this evolutionary pressure, we compared the properties of rat and chicken recombinant and native a9a10 receptors. Our main finding in the present work is that, in contrast to the high (pCa(2+)/pMonovalents 10) Ca(2+) permeability reported for rat a9a10 receptors, recombinant and native chicken a9a10 receptors have a much lower permeability (2) to this cation, comparable to that of neuronal ¥á4¥â2 receptors. Moreover, we show that, in contrast to a10, a7 as well as a4 and a2 nicotinic subunits are under purifying selection in vertebrates, consistent with the conserved Ca(2+) permeability reported across species. These results have important consequences for the activation of signaling cascades that lead to hyperpolarization of hair cells after a9a10 gating at the cholinergic-hair cell synapse. In addition, they suggest that high Ca(2+) permeability of the a9a10 cholinergic nicotinic receptor might have evolved together with other features that have given the mammalian ear an expanded high-frequency sensitivity.